Ventricular Fibrillation Arrest after Blunt Chest Trauma in a 33-year-old Male, Commotio Cords? - pena, clarissa (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.